Watch and wait management of inactive cystic echinococcosis: does the path to inactivity matter : analysis of a prospective patient cohort - Stojković, Marija; Rosenberger, Kerstin; Junghanss, Thomas (PLoS neglected tropical diseases, 2016)
Author Summary Cystic echinococcosis (CE) is a zoonosis of worldwide distribution causing cystic lesions in the liver and lung. The prevalence of disease is highest in countries with limited resources. Overdiagnosis and overtreatment are increasingly discussed in medical practice not surprisingly also for patients with cystic echinococcosis. In neglected tropical diseases (NTD) this is particularly relevant since most patients are under the care of health services with limited resources where the risk of therapy induced complications are often disproportionate to the benefit of interventions. Our study aims at answering the following Questions: Do inactive cysts (CE 4 and CE 5) need treatment and is there a difference between cysts which reach CE4 and CE5 naturally or by benzimidazole therapy? Results of our study impressively show that a substantial proportion of patients can be spared from any treatment through cyst staging. Cysts which inactivated through a natural course of involution do not relapse with very high likelihood. To rule out unlikely events, we recommend follow up of 5 years to confirm the stability of the inactive stage. Cysts driven into inactivity instead need careful monitoring to identify those which reactivate (around 50% within 18 months). 5 years follow-up appears safe to make a final decision.
Gesehen am 26.09.2016